KARAKTERISTIK AUDITOR, RISIKO AUDIT, DAN TANGGUNG JAWAB DALAM MENDETEKSI KECURANGAN - Andenna Pentaza Swastyami (Jurnal Akuntansi Bisnis, 2016)
This study investigate the relation between auditor characteristics and audit risk with its responsibilities to detect fraudulent financial statements. This study predicts auditor independence, auditor competence and ethical awareness are positively related to auditor's responsibility to detect fraudulent financial statements. Linear regression analysis is employed to test the hypothesis with following results: (1) Independence is positively related to auditor's responsibilities in detecting fraud. (2) Competence is positively related to auditor's responsibility to detect fraud. (3) Audit risk is positivele related to auditor's responsibility to detect fraud. (4) Ethical awareness is not related to auditor's responsibility in detecting fraud